Day 5 Wed, April 18, 2018 2018
DOI: 10.2118/190165-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Successful Polymer Flood Pilot at Palogrande-Cebu, A Low Permeability Reservoir in the Upper Magdalena Valley, Colombia

Abstract: Palogrande-Cebu is a mature clastic field located in the south of Colombia and part of the production train of the Monserrate Formation that has several fields and presents an OOIP about 1000 MMBBLs. In these fields Ecopetrol have been tested different chemical EOR/IOR technologies like polymer flooding, CDG and conformance treatments with encouraging results. Palogrande field has been in production since 1971, and under peripheral water injection since 1984, with a recovery factor of 28%. The reservoir has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…The polymers can maintain a viscosity of 2-3 cP (2500-4000 mg/L), with good injection and enhanced oil recovery effects. Leon et al [27] reported a successful field pilot of the polymer in the low-permeability Palogrande-Cehu field. Considering the low permeability of the reservoir (6-150 mD), three polymers with different molecular weights (average concentration 1021 mg/L, viscosity 3.43 cP) were used, and the viscosity change was monitored.…”
Section: Introductionmentioning
confidence: 99%
“…The polymers can maintain a viscosity of 2-3 cP (2500-4000 mg/L), with good injection and enhanced oil recovery effects. Leon et al [27] reported a successful field pilot of the polymer in the low-permeability Palogrande-Cehu field. Considering the low permeability of the reservoir (6-150 mD), three polymers with different molecular weights (average concentration 1021 mg/L, viscosity 3.43 cP) were used, and the viscosity change was monitored.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer is developed from inorganic profile control agents such as clay, fly ash, and cement to organic gel profile control agents in the 1970s. Although polymer flooding has made great progress [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], due to its small injection volume and small treatment radius, it can only play a certain role in the longitudinal heterogeneity near-well zone, and it is only a production measure, strictly speaking. In order to solve the limitation that polymer flooding can only be used in the near-well area.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional and mature EOR technologies based primarily on polymer (HPAM) include polymer flooding, surfactantpolymer flooding (SP), alkaline-surfactant-polymer flooding (ASP), and crosslinked polymer gel flooding. ese technologies have achieved significant success worldwide [1][2][3][4][5][6][7][8][9]. However, the temperature and salinity resistance of the polymer is limited, and as a continuous phase high viscosity fluid, its mechanism of oil displacement is also contradictory [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%